Consumption of foods with the Keyhole front-of-pack nutrition label: potential impact on energy and nutrient intakes of Swedish adolescents. Issue 12 (30th December 2022) - Wanselius, Julia; Larsson, Christel; Berg, Christina; Öhrvik, Veronica; Lindroos, Anna Karin; Lissner, Lauren
Abstract: Objective: The Keyhole is an internationally recognised front-of-pack nutrition label, guiding consumers to healthier food options. It indicates products in accordance with specific criteria for dietary fats, sugars, fibres, salt and wholegrains. The objective of this study was to simulate the potential impact of the Keyhole on adolescents' energy and nutrient intakes by modelling a shift from reported food intakes to foods meeting the Keyhole criteria. Design: Self-reported dietary intake data were derived from a cross-sectional survey. Multiple replacement scenarios were calculated, where foods meeting the Keyhole criteria replaced reported non-compliant foods with varying proportions of replacement. Setting: Dietary survey 'Riksmaten Adolescents 2016–2017' in schools across Sweden. Participants: A nationally representative sample of 3099 adolescents in school years 5, 8 and 11 (55 % girls). Results: Overall, replacement with foods meeting the Keyhole criteria led to more adolescents meeting nutrition recommendations. Largest median intake improvements were seen for wholegrains (+196 %), SFA (-13 %), PUFA (+17 %) and fibres (+15 %). Smallest improvements were seen for free sugars (-3 %) and salt (-2 %), partly explained by the ineligibility of main food sources of free sugars for the Keyhole, and non-inclusion of ready meals that are often high in salt. Most micronutrient intakes were stable or improved. Unintentional effects included decreases in vitamin A, MUFA and energy intakes. Largest potential improvements in fat and fibre sources were observed in the youngest age group. Conclusions: A shift to Keyhole alternatives for everyday foods would improve adolescents' nutrient intakes, even with smaller exchanges.